Statistical analysis of climate change indicators in Najaf Governorate, Iraq (Journal of Human Sciences, 2021)
This research aims to determine the indicators of climate change in the province of Najaf in Iraq by analyzing the data on the seasonal and annual rates of temperature (minimum, maximum and dry) and the quantities of seasonal and annual rainfall to determine the general trend and dry years and their change for the period from 1987-2019, Using statistical analysis methods in climate studies to detect trends in climate change, such as Simple Linear Regression and t-test. The results showed trends of change in annual and seasonal temperature at a statistical significance level of less than 0.001, While there was a decrease in the annual rainfall amounts without statistical significance with the increase of dry years during the second period of the study in Najaf Governorate. With the emergence of different trends in the seasonal rates of temperature and at the level of statistical significance that ranged between 0.001 to 0.05, while the change in seasonal rain trends was varied between increase and decrease and without statistical significance.